2004
DOI: 10.1063/1.1835566
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature oxidation kinetics of Si nanoparticles in air, determined by x-ray photoelectron spectroscopy

Abstract: The air oxidation kinetics of low coverages of ϳ5 nm Si nanoparticles, deposited by pulsed excimer laser ablation (KrF, 248 nm) in He, have been characterized by x-ray photoelectron spectroscopy. A simple model, based on the evolution of the Si 2p spectral components during oxidation, has been developed to determine the nanoparticle oxide thickness. It is found that the short-term oxide thickness is greater, and the long-term room-temperature air oxidization rate of these nanoparticles is less, than those repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 44 publications
3
115
0
1
Order By: Relevance
“…One way is to use a simple attenuation factor through the shell where d is the thickness of the silica shell and λ S and λ C are the attenuation lengths of the core and the shell, respectively. The extended formula derived by Yang et al 33 is similar to eq 2 but also includes additional terms where κ(x) is another function containing several other terms. Two points are relevant to our discussion below: (i) the additional term in eq 3 is always smaller than 1, and (ii) eq 3 yields eq 1 when d ) 0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One way is to use a simple attenuation factor through the shell where d is the thickness of the silica shell and λ S and λ C are the attenuation lengths of the core and the shell, respectively. The extended formula derived by Yang et al 33 is similar to eq 2 but also includes additional terms where κ(x) is another function containing several other terms. Two points are relevant to our discussion below: (i) the additional term in eq 3 is always smaller than 1, and (ii) eq 3 yields eq 1 when d ) 0.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 In a very recent paper, the same group extended the formula, derived for a simple spherical particle by Wertheim and DiCenzo, for application to particles with a spherical core and a uniform shell and studied the oxidation kinetics of Si nanoparticles by XPS. 33 In most of the previous reports, only one element was probed by XPS to extract information about the structure of the core-shell nanoparticles. It is, however, desirable to probe by XPS different elements belonging to the core and the shell separately in order to extract more complete structural information, which eliminates many of the experimental sources of error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference should not result from the differences in size of the NCs in the two samples. In previous studies, shorter induction periods have been observed for nanoparticles (curved Si surface) in comparison to flat surfaces of bulk silicon, 44 due to the increasingly higher number of oxidation sites present in increasingly curved surfaces. Thus, the somewhat smaller size of the NCs in the LIDD samples would result in a shortened induction period in comparison to MIDD Si-NCs, which is in clear contrast with our experimental results.…”
Section: 29mentioning
confidence: 99%
“…Determining oxidation and corrosion rates for nanoparticles is somewhat more complex than determining corrosion rates for larger flat samples. [21] Here we compare the oxidation rates of two differently sized nanoparticles, prepared by two different processes, in DI water. Reactivity studies conducted on these particles show significantly different reaction rates.…”
Section: Time-dependent Properties Of Fe Nanoparticlesmentioning
confidence: 99%